Management of edoxaban in patients undergoing multiple procedures: a subanalysis of the EMIT-AF/VTE program. (19th May 2022) - Saxena, M; Von Heymann, C; Santamaria, A; Jin, J; Chen, C; Borrow, A; Vanassche, T; Unverdorben, M; Colonna, P
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Daiichi Sankyo Background: Patients with atrial fibrillation (AF) or venous thromboembolism (VTE) receiving long-term direct oral anticoagulant (DOAC) therapy undergo diagnostic or therapeutic procedures at a rate of approximately 10% annually. The prospective Global EMIT-AF/VTE program (Edoxaban Management in Diagnostic and Therapeutic Procedures; NCT02950168, NCT02951039) demonstrated that physician-guided periprocedural management of the DOAC edoxaban in these patients was associated with low bleeding and thromboembolic event rates. It is unclear whether the experience of a previous (index) procedure influences the periprocedural management of subsequent procedures. Purpose: To analyze differences in periprocedural edoxaban management in patients on chronic anticoagulation therapy undergoing multiple diagnostic or therapeutic procedures. Methods: Baseline characteristics were recorded in patients enrolled in the EMIT-AF/VTE program who underwent multiple procedures. Details of periprocedural edoxaban interruption were collected from patients who underwent two procedures of the same European Heart Rhythm Association (EHRA) bleeding risk level or procedural type. Only data from the index and second procedure of the same category were included in this analysis; procedures conducted less than 7 days apart were excluded. All analyses are exploratory and descriptive in nature. Results: Among 227 patients who underwent multiple procedures, the most common types were vascular and gastrointestinal (GI) procedures. Patients had a mean ± standard deviation age of 72.1 ± 9.8 years, a CHA2DS2-VASc score of 3.2 ± 1.6, a HAS-BLED score of 1.9 ± 1.0, and were mostly male (67.0%). Patients who underwent low/minor risk procedures were less likely to undergo edoxaban interruption with their second procedure compared with their index procedure (Figure 1A), and the median interruption duration was shorter for the second procedure (Table 1). A second high risk procedure was associated with a higher rate of both pre- and postprocedural edoxaban interruption compared with a patient's index procedure, but treatment resumed earlier (Figure 1B). Patients who underwent vascular procedures had a lower rate of pre- and postprocedural interruption and a shorter interruption time with their second procedure (Table 1). Conversely, patients who underwent GI procedures experienced pre- and postprocedural interruption more often for their second procedure. The median interruption duration was longer for GI procedures than for vascular procedures (Table 1). Conclusion: Overall, periprocedural edoxaban interruption varied by procedural bleeding risk and type. Edoxaban interruption patterns differed between index and second procedures, indicating that periprocedural edoxaban management may be influenced by the experience of previous procedures.